A Summary of “Die Wiedergutmachung nationalsozialistischen Unrechts durch die Bundesrepublik Deutschland Band III – Der Werdegang des Entschädigungsrechts” - Hagjija-Alaoui, Hanin; Justus Liebig University Giessen (My University, 2024)
The following article provides a brief summary of the third volume of the series “Die Wiedergutmachung nationalsozialistischen Unrechts durch die Bundesrepublik Deutschland” published, among others, by the Federal Ministry of Finance in six volumes, and is accordingly focused on the general development of compensation law.
Keywords: ddc:340